2010
DOI: 10.1007/s11069-010-9531-8
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude conversion problem for the Turkish earthquake data

Abstract: Earthquake catalogues which form the main input in seismic hazard analysis generally report earthquake magnitudes in different scales. Magnitudes reported in different scales have to be converted to a common scale while compiling a seismic data base to be utilized in seismic hazard analysis. This study aims at developing empirical relationships to convert earthquake magnitudes reported in different scales, namely, surface wave magnitude, M S , local magnitude, M L , body wave magnitude, m b and duration magnit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…In the same study, for the saturation problem of some earthquake magnitudes (for instance, M S ) detailed analyses were carried out. Besides, the distributions of earthquakes due to different earthquake catalogs within the same earthquake scale and among different magnitude scales were investigated (DENIZ and YUCEMEN, 2010). As a result, we found that the surface wave magnitude results of KOERI were overestimating the earthquake magnitude with respect to the other data sources.…”
Section: The Earthquake Databasementioning
confidence: 93%
See 1 more Smart Citation
“…In the same study, for the saturation problem of some earthquake magnitudes (for instance, M S ) detailed analyses were carried out. Besides, the distributions of earthquakes due to different earthquake catalogs within the same earthquake scale and among different magnitude scales were investigated (DENIZ and YUCEMEN, 2010). As a result, we found that the surface wave magnitude results of KOERI were overestimating the earthquake magnitude with respect to the other data sources.…”
Section: The Earthquake Databasementioning
confidence: 93%
“…As a result, we found that the surface wave magnitude results of KOERI were overestimating the earthquake magnitude with respect to the other data sources. To overcome this problem, the so called intra-scale conversion relationships were developed and the earthquake catalog was homogenized before converting all the magnitudes into moment magnitude (DENIZ and YUCEMEN, 2010).…”
Section: The Earthquake Databasementioning
confidence: 99%
“…On the other hand, a Moment Magnitude (Mw) is preferred because of its applicability for all ranges of earthquakes; large or small, far or near, shallow or deep focused. In or- der to construct a homogeneous earthquake catalog, a moment magnitude-duration magnitude relationship of [30] was used in this study.…”
Section: Data Processingmentioning
confidence: 99%
“…The conversion is performed using the equation derived by Deniz and Yücemen (2010) based on earthquakes recorded in Turkey, which is given as follows:…”
Section: Seismic Database and Seismic Sourcesmentioning
confidence: 99%